Colour image encryption based on logistic mapping and double random‐phase encoding. Issue 4 (1st April 2017) - Huang, Huiqing; Yang, Shouzhi
Abstract : In this study, the authors propose a novel method to encrypt a colour image by use of Logistic mapping and double random‐phase encoding. Firstly, use Logistic mapping to diffuse the colour image, then the red, green and blue components of the result are scrambled by replacement matrices generated by Logistic mapping. Secondly, by utilising double random‐phase encoding to encrypt the three scrambled images into one encrypted image. Experiment results reveal the fact that the proposed method not only can achieve good encryption result, but also that the key space is large enough to resist against common attack.